Programa educativo de juegos en el mejoramiento de la expresión oral en inglés en estudiantes de segundo grado de secundaria de la institución educativa primaria secundaria Rosa Agustina Donayre de Morey, Iquitos 2019 - Lopez Velasquez, Naysha Margot (2021)
The objective of this research study was to assess the effectiveness of a learner-training program based on games to improve second grade students’ speaking skills at Rosa Agustina Donayre de Morey high school, Iquitos 2019. The research type was experimental and quasi experimental design with pre-test, post-test and control group. The population was made up by 359 students and a deterministic sample of 64 students divided into two groups: experimental group with 30 students and the control group with 34 students. The data gathering tool was a speaking performance test, validated by experts with a reliability score of 81.7% Cronbach Alpha. The post test results showed that the experimental group outperformed the control group as their mean scores were 13,64 > 10,93. Therefore, the learner-training program based on games improved significantly the population students’ speaking skills (p-value = 0,000) and its indicators: pronunciation (p-value = 0,000), fluency (p-value = 0,000), grammar (p-value = 0,000), vocabulary (p-value = 0,000) and body language (p-value = 0,011), accepting the working hypotheses.